Post‐mortem Iris Decomposition and its Dynamics in Morgue Conditions - Trokielewicz, Mateusz; Czajka, Adam; Maciejewicz, Piotr (Journal of forensic sciences, 2020)
With increasing interest in employing iris biometrics as a forensic tool for identification by investigation authorities, there is a need for a thorough examination and understanding of postmortem decomposition processes that take place within the human eyeball, especially the iris. This can prove useful for fast and accurate matching of antemortem with postmortem data acquired at crime scenes or mass casualties, as well as for ensuring correct dispatching of bodies from the incident scene to a mortuary or funeral homes. Following these needs of forensic community, this paper offers an analysis of the coarse effects of eyeball decay done from a perspective of automatic iris recognition. We analyze postmortem iris images acquired for a subject with a very long postmortem observation time horizon (34 days), in both visible light and near‐infrared light (860 nm), as the latter wavelength is used in commercial iris recognition systems. Conclusions and suggestions are provided that may aid forensic examiners in successfully utilizing iris patterns in postmortem identification of deceased subjects. Initial guidelines regarding the imaging process, types of illumination, and resolution are also given, together with expectations with respect to the iris features decomposition rates. Visible iris features possible for human, expert‐based matching persists even up to 407 h postmortem, and near‐infrared illumination is suggested for better mitigation of corneal opacity while imaging cadaver eyes (Post‐mortem iris decomposition and its dynamics in morgue conditions. ArXiv pre‐print, 2019).